AN APPLIED STUDY OF INDUSTRIAL COMPANIES LISTED ON THE IRAQ STOCK EXCHANGE (World Economics and Finance Bulletin, 2025)
The research aimed to estimate the role that artificial intelligence technologies can play in improving the performance of economic development plans for a sample of industrial companies listed on the Iraq Stock Exchange. Artificial intelligence has become one of the most important tools supporting the economic decision making process, due to its advanced capabilities in analyzing big data, predicting future trends, and monitoring potential risks in complex and changing business environments. The research relies on a descriptiveanalytical approach based on financial and administrative data from a number of listed Iraqi industrial companies, employing some applied AI models in areas such as resource management, improving operational efficiency, and strategic planning. The results showed that integrating artificial intelligence into economic planning and development processes contributes to enhancing the competitiveness of industrial companies, supporting their ability to cope with market fluctuations, and providing a more stable investment environment. The research also demonstrated that adopting these technologies is not limited to increasing profits alone, but also includes improving the quality of administrative decisions and developing sustainable growth strategies in line with the requirements of the next phase of economic development in Iraq.